Electronic structure and magnetostrictive sensitivity of Fe-B metallic glasses - Beznosov, A. B.; Fertman, E. L.; Eremenko, V. V.; Desnenko, V. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The effect of mechanical tensile stresses 0 ≤ s ≤ 62 MPa on the low-field (0 ≤ H ≤ 45 Oe) magnetization curves of the metallic glasses Fe100-xBx (x=14, 16, 17, 20) is studied at temperatures of 77 and300 K. The correlation between the electronic structure of the glasses and their magnetostrictivesensitivity ks is revealed: the eutectic metallic glass Fe83B17, which possesses a special electronic structure with a 30% lower conduction (sp) electron density, has a value of ks differing substantially from that of the other metallic glasses studied. Under low stresses (0 ≤ s ≤ 22 MPa) the eutectic alloy possesses a magnetostrictive sensitivity ks(s1) which is higher than that of the rest of the alloys studied,while under high stresses (22 MPa ≤ s ≤ 62 MPa) its magnetostrictive sensitivity ks(s2) is close to zero.